2006
DOI: 10.1002/app.23821
|View full text |Cite
|
Sign up to set email alerts
|

Fractal model of the heat conductivity for carbon fiber‐reinforced aromatic polyamide

Abstract: It is shown that the heat conductivity of carbon fiber (CF)-reinforced aromatic polyamide on the basis of phenylone can be described within the framework of a fractal model. Depending on the dimension of filler fibers network (system), such description can be obtained by the application of two limiting cases: random network of resistors (RNR) or random superconducting network (RSN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…al. [76] formed carbon fiber reinforced aromatic polyamide network. Two types of polyamide/CF networks were developed: random superconducting network and random network of resistors.…”
Section: Aromatic Polyamide/carbon Fibermentioning
confidence: 99%
“…al. [76] formed carbon fiber reinforced aromatic polyamide network. Two types of polyamide/CF networks were developed: random superconducting network and random network of resistors.…”
Section: Aromatic Polyamide/carbon Fibermentioning
confidence: 99%
“…Studies show that fiber preform is a fractal. [37][38][39] Thus, based on fractal theory, fiber preform satisfies the following equations 28 NðÞ¼…”
Section: The New Fractal Modelmentioning
confidence: 99%
“…Studies show that fiber preform is a fractal. 3739 Thus, based on fractal theory, fiber preform satisfies the following equations 28 where p(λ) is a density function of the equivalent diameter and L represents the characteristic quantity that is used to describe a fractal medium. L 0 is the representative length of a channel, L t ( λ ) is the physical length of the channel of which equivalent diameter equals λ (see Figure 3), ϕ is the porosity of the porous medium, λ is the equivalent diameter of a tortuous channel, and N ( λ ) the number of channels whose diameters are greater than λ .…”
Section: Modeling Processmentioning
confidence: 99%
“…The authors of Refs [152,153] demonstrated in the framework of the above general model that the two main cases hold for polymer composites filled with short fibers. For D B`2 X62 (RSN limit), the dependence l T D B is approximated by the following equation…”
Section: Thermophysical Propertiesmentioning
confidence: 99%